REVITALISASI GENDING-GENDING BANVUMAS DALAM GAMELAN CALUNG SEBUAH TAWARAN KARYASENI - Darno Darno (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2006)
This work is a bid to revitalize traditional Banyumas compositions for calung gamelan, an effort to enable the re-emergence of a traditional art form which has recently been deemed to have become extinct. The musical works are the composers attempt, in so far as is possible, to interpret and rediscover the depth of potential of calung and traditional Banyumas compositions in an innovative way. Traditional Banyumas compositions for calung which are typically performed in a careful, static manner, both rhythmically and melodically, are presented here in a more energetic and varied way. Various dynamic processes such as irama [rhythym], tempo, melodic contour and register are explored as well as using more established and transparent techniques. Through these processes, the composer makes a deliberate effort to create a system whereby other musicians can easily learn and imitate the techniques presented in these works.Keywords : Revitalitation, Calung, Alternative